Archaeological evidence for population rise and collapse between ~2500 and ~500 cal. yr BP in Western Central Africa - de Saulieu, G; Garcin, Y; Sebag, D; Zeitlyn, D (Archéologie et Sciences de l'Antiquité, 2021)
Palaeocological studies show that major vegetation and environmental changes occurred in Central Africa from the mid-Holocene (e.g. Maley & Brenac 1998). Several suggest a human origin and assume that large population migration, technical innovations (e.g. iron-smelting technology) and/or change in agricultural practice, leading to deforestation and land clearance, are the drivers of these changes. However, at this stage, the lack of demographic reconstruction does not fully support these hypotheses. Here, a georeferenced archaeological database is used to infer population dynamics and the evolution of cultural practices in Western Central Africa over the last 5000 years. This database includes 1139 14C calibrated dates from 425 sites throughout southern Cameroon, Gabon, the Republic of Congo, Equatorial Guinea and the western part of the Democratic Republic of Congo, dating back a maximum of 5000 cal. yr BP. Data modelling indicate possible population growth from 2500 to 1500 cal. yr BP, coinciding with the occurrence at a regional scale of specific techniques and practices. The concomitant increase of refuse pits, palm oil Elaeis guineesis and iron metallurgy (plus rare remains of millet Pennisetum glaucum) took place during the second half of the Neolithic, beginning around 2800 cal. yr BP. In the coastal regions, the population growth concerns the Neolithic and the Early Iron Age (2500–2000 cal. yr BP and 2000–1500 cal. yr BP), while in the Hinterland population growth seems slightly later (2400 and 1300 cal. yr BP). It is not possible to identify a common diffusion phenomenon from a single homeland. Rather, technical innovations and new practices appear to have spread through a wide network of cultural interactions, which fostered the formation of Western Central African societies during the third millennium.